The Role of Local Folklores in Students’ Reading Comprehension - Monica, Monica; Soplantila, Eduard (MATAI: International Journal of Language Education, 2024)
This paper aims to the role of local folklores in students’ reading comprehension. This paper is expected to be used as guidance by English teacher in teaching and learning, especially to improve students’ reading comprehension. The topic being discussed in this paper are limited only to the role of local folklores in students’ reading comprehension. Researches showed that local folklores improving students reading comprehension, also using local folklore can be an effective way to engage students and help them develop their reading comprehension skills. By using stories and legends that are familiar to students, teachers can help them connect with the material and develop a deeper understanding of the narrative. Additionally, local folklore can provide a window into the culture and traditions of the community, helping students develop a sense of pride and appreciation for their heritage. This can further motivate them to learn and improve their reading skills. However, it's important to note that the effectiveness of using local folklore will depend on the specific context and the quality of the instructional design. Teachers need to carefully select appropriate materials and design activities that align with the learning objectives and meet the needs of their students. In conclusion, the use of local folklore can be a valuable tool for improving students' ability in reading comprehension.